Cocoa Pulp as Alternative Food Matrix for Probiotic Delivery - Guimarães, Gabriele M.; Soares, Letícia A.; Silva, Tuânia N.L.; de Carvalho, Iracema L.Q.; Valadares, Helder M.S.; Sodré, George A.; Gonçalves, Daniel B.; Neumann, Elisabeth; Da Fonseca, Flávio G.; Vinderola, Gabriel; Granjeiro, Paulo A.; de Magalhães, Juliana T. (Recent Patents on Food, Nutrition & Agriculture, 2020)
Background: For screening probiotic strains with viability and stability in non-dairy foods for health benefits, we revised all patents relating to probiotics in food. Objective: Screening of potential probiotics from Brazilian Minas artisanal cheese and verify their survival in frozen Brazilian cocoa pulp. Methods: Isolation and identification of the strains. The potential probiotic characterization involved gastric juice and bile resistance, antibiotic and antimicrobial activity, hydrophobicity, autoaggregation, coaggregation and adhesion assay in HT-29 cells. Organoleptic, viability and stability of probiotic strain in frozen cocoa pulp were evaluated. Results: Fourteen strains of Lactobacillus plantarum (9), Weissella paramesenteroides (3), Lactobacillus fermentum (1), and Leuconostoc mesenteroides (1) were obtained. Most of the strains were resistant to simulated gastric acidity and bile salts. Almost all strains were sensitive to the antibiotics tested, except to ciprofloxacin and vancomycin. About 47% of the strains are potential producers of bacteriocins. High hydrophobicity was observed for four strains. Autoaggregation ranged from 8.3-72.6% and the coaggregation capacity from 5.2-60.2%. All of the assessed strains presented more than 90% of adhesion to HT-29 intestinal cells. The percentage of Salmonella inhibition in HT-29 cells ranged from 4.7-31.1%. No changes in color, aroma, and pH were observed in cocoa pulps after storage at -20 °C for 90 days. Conclusion: Wild strains of acid lactic bacteria from cheese proved to be viable and stable in frozen Brazilian cocoa pulp. This work showed a promising application of L. plantarum isolated strains to be used with frozen cocoa pulp matrix in probiotics food industry.
Keywords: cheese